Correction: A challenge for theranostics: is the optimal particle for therapy also optimal for diagnostics?. Issue 33 (8th August 2016) - Dreifuss, Tamar; Betzer, Oshra; Shilo, Malka; Popovtzer, Aron; Motiei, Menachem; Popovtzer, Rachela
Abstract : Correction for 'A challenge for theranostics: is the optimal particle for therapy also optimal for diagnostics?' by Tamar Dreifuss, et al., Nanoscale, 2015, 7, 15175–15184.